ANAK ANGKAT MENURUT HUKUM POSITIF - Sibawaih, Muhammad (LPPM-IAI BATAM, 2025)
In Indonesia, an adopted child is a child whose daily livelihood is transferred from his or her biological parents to his or her adoptive parents based on a court decision. However, until now, there are still a number of dynamics related to the process of child adoption in Indonesia. In the context of positive law, child adoption is allowed. However, there are a number of processes that must follow legal procedures. Furthermore, once the court decides to grant child adoption, the child becomes an adopted child in both positive and Islamic law. After the adopted child officially becomes an adopted child and lives with his or her adoptive parents, the adopted child must have a good and proper position in the adoptive parents' home